Spectral Methods to Investigation the Stability for Parabolic Problems (Journal of the College of Basic Education, 2023)
In this paper, the formula of second order parabolic problems with finite difference method (mesh method) has been presented and we used the spectral method to investigate the stability for parabolic problems.